Comparison of periapical parallel radiography with cbct with different field of views (FOV) for the detection of periapical lesions (Dental Research Journal)
Background: Chronic apical periodontitis (AP) may influence the outcome of root canal treatment. Thus, it is important to diagnose AP using the best method available. This research was done to compare the diagnostic accuracy of parallel periapical radiography (PR) and different field of views (FOVs) of cone-beam computed tomography (CBCT). Materials and Methods: This ex vivo study was done on six human mandibles. After extraction of the teeth, periapical lesions with different sizes were prepared randomly by drilling a hole at the base of the socket using a bur. From among 67 sockets, 21 sockets had no lesion (control); then, all mandibles were scanned by CBCT with different FOVs and paralleling periapical technique radiography. The images were assessed by two examiners. The quantitative data were analyzed by intraclass correlation coefficient (ICC) and the qualitative data were analyzed by McNemar’s test (α = 0.05). Sensitivity, specificity, and accuracy were calculated. Inter-observer agreement was assessed using kappa statistics for qualitative data and ICC for quantitative data. Results: The quantitative scores were compared with the gold standard using ICC, which showed maximum agreement for the dental FOV of CBCT (93.3) and minimum agreement for PR (62.5) (P < 0.001). For qualitative data, maximum agreement was found for the dental FOV of CBCT (97.1%), and minimum agreement was reported for PR (59.7%). Kappa values were variable between 0.271 and 0.924 (P < 0.001). Maximum sensitivity was found for the dental FOV of CBCT (96%) and minimum sensitivity was observed for PR (51%). The inter-observer agreement was 0.922 for qualitative data and 0.90 for quantitative data (P < 0.001). There were no significant differences between CBCT with different FOVs and defect sizes (gold standard) while we found significant differences for periapical by defect sizes. Conclusion: CBCT with dental FOV presents the highest sensitivity and diagnostic accuracy for detection and characterization of simulated AP.